2014
DOI: 10.1007/s10530-014-0815-x
|View full text |Cite
|
Sign up to set email alerts
|

Fast-growing and poorly shade-tolerant invasive species may exhibit higher physiological but not morphological plasticity compared with non-invasive species

Abstract: Phenotypic plasticity is one of the important mechanisms relevant to exotic plant invasions, and high plasticity is likely to influence the potential invasiveness of species. Phenotypic plasticity is broadly defined as the ability of organisms to alter their morphological and/or physiological traits in response to varying environments. Morphological and physiological plasticity are thought to have different mechanisms, resource costs and ecological implications. However, our understanding on how morphological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 49 publications
3
19
0
Order By: Relevance
“…However, this was not always connected with higher variability of alien species traits along resources availability gradients, which may indicate high variability of trait values within young generations of invasive species. Most previous studies revealed differences in phenotypic plasticity between alien and native species (Paquette et al 2012;Lamarque et al 2013;Hou et al 2014). Kuehne et al (2014) did not find differences in phenotypic plasticity of Q. rubra and three co-occurring native species.…”
Section: Trait Variabilitymentioning
confidence: 72%
“…However, this was not always connected with higher variability of alien species traits along resources availability gradients, which may indicate high variability of trait values within young generations of invasive species. Most previous studies revealed differences in phenotypic plasticity between alien and native species (Paquette et al 2012;Lamarque et al 2013;Hou et al 2014). Kuehne et al (2014) did not find differences in phenotypic plasticity of Q. rubra and three co-occurring native species.…”
Section: Trait Variabilitymentioning
confidence: 72%
“…inermis , did not differ in R/S, plant height and plasticity of these traits in response to nutrient addition or shading. Some previous studies showed that highly invasive and less invasive exotic plants differed in some functional traits or trait plasticities (Skálová et al ., ; Hou et al ., ), although others did not find this pattern (Kattia & Ernesto, ; Dawson et al ., 2012b; Ruprecht et al ., ). It is possible that the subspecies M. invisa var.…”
Section: Discussionmentioning
confidence: 92%
“…For example, the biomass and plant height of invasive plants increased (Huang et al ., ; Chen & Chen, ), and the ratio of root to shoot decreased with increasing soil nutrient availability (Huang et al ., ). Under the condition of low light, the biomass and ratio of root to shoot decreased significantly (Hou et al ., ; Huang et al ., ; Yasin et al ., ). Highly invasive plants may be more plastic than less invasive plants in some functional traits, which makes the highly invasive plants respond more positively to changes in environmental conditions and outperform the latter in at least some environments (Hastwell & Panetta, ; Richards et al ., ; Verlinden et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…An important invasion mechanism of successful invasive species is the ability of invasive species to outperform co-occurring non-invasive species in trait values and/or trait plasticity1921272852. Advantageous trait values enable invasive species to outcompete non-invasive species and thus facilitate the establishment of invasive species in recipient habitats819.…”
Section: Discussionmentioning
confidence: 99%
“…Empirical studies have indicated that phenotypic plasticity plays a significant role in biological invasions172425262728. Adaptive plasticity enables species to extend ecological niche breadth as plastic responses promote advantageous trait expressions in different environments232930.…”
mentioning
confidence: 99%